The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1007/s10545-013-9654-7
|View full text |Cite
|
Sign up to set email alerts
|

Galsulfase (Naglazyme®) therapy in infants with mucopolysaccharidosis VI

Abstract: ObjectiveTo evaluate the efficacy and safety of two dose levels of galsulfase (Naglazyme®) in infants with MPS VI.Study designThis was a phase 4, multicenter, multinational, open-label, two-dose level study. Subjects were randomized 1:1 to receive weekly infusions of 1.0 or 2.0 mg/kg of galsulfase for a minimum of 52 weeks. Progression of skeletal dysplasia was determined by monitoring physical appearance, radiographic changes, and growth. Urinary glycosaminoglycan (GAG) levels, gross and fine motor function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Aggregated data from patients who had initiated ERT when less than 5 years of age showed that over 50% of patients were below the 3rd percentile for height, although one girl was above the 97th percentile. Comparing baseline height prior to initiation of ERT to height at the end of the study, 37.5% patients remained on the same percentile growth curve, 9.4% improved to a percentile curve above and 53% fell below their original percentile curve, suggesting that growth is not normalized by ERT [63][64][65].…”
Section: Enzyme Replacement Therapy (Ert)mentioning
confidence: 98%
“…Aggregated data from patients who had initiated ERT when less than 5 years of age showed that over 50% of patients were below the 3rd percentile for height, although one girl was above the 97th percentile. Comparing baseline height prior to initiation of ERT to height at the end of the study, 37.5% patients remained on the same percentile growth curve, 9.4% improved to a percentile curve above and 53% fell below their original percentile curve, suggesting that growth is not normalized by ERT [63][64][65].…”
Section: Enzyme Replacement Therapy (Ert)mentioning
confidence: 98%
“…Aggregated data from patients who had initiated ERT when less than 5 years of age showed that over 50% of patients were below the 3rd percentile for height, although one girl was above the 97th percentile. Comparing baseline height prior to initiation of ERT to height at the end of the study, 37.5% patients remained on the same percentile growth curve, 9.4% improved to a percentile curve above and 53% fell below their original percentile curve, suggesting that growth is not normalized by ERT [63-65]. …”
Section: Therapies For Bonementioning
confidence: 99%
“…ERT for other lysosomal diseases, such as rGALNS for mucopolysaccharidosis VIA 34 and rARSB for mucopolysaccharidosis VI 35 , also have poor delivery to diseased non-CNS organs partially due to the limitations of CI-MPR 36 . Enzyme delivery to address the skeletal phenotypes in mucopolysaccharidoses I-VII remains a challenge due to the virtually nonexistent delivery to these tissues 37 .…”
Section: Conceptually Any Transmembrane or Cell Surface Protein Thatmentioning
confidence: 99%